Penerapan Metode Estafer Writing Penerapan Metode Estafet Writing Untuk Meningkatkan Keterampilan Menulis Puisi Mata Pelajaran Bahasa Indonesia Di X Akuntansi SMK Muhammadiyah Larangan: Metode Estafet Writing Meningkatkan Keterampilan Menulis Puisi - Finanti, Asyah; Santosa, Budi (Jurnal Korpus, 2023)
The purpose of this study was to improve the skills of students in learning to write poetry using the relay writing  in class X Accounting at the Muhammadiyah Vocational School of Prohibition Brebes in the odd semester of the 2022/2023 academic year. The type of research used is qualitative research with a PTK research approach (classroom action research). Classroom action research is part of the activities carried out by the teacher and directed by the teacher regarding a material in the learning process in class. This classroom action research uses the Taggart model. In the Taggart model there are 4 stages, namely planning, observing, observing and reflecting. This research was conducted with II cycle. The research was conducted in December 2022. With 26 students as research subjects. The results showed that there was an increase in skills in writing poetry using the relay writing method. It can be seen from cycle I consisting of 6 groups with 9 students who completed and 17 students who did not complete. in poetry writing skills, while in cycle II there were 6 groups with a total of 16 students who completed poetry writing skills and 10 students in cycle II who did not complete poetry writing.